Hyperkalemia as a limiting factor of Neurohormonal Blockade/Modulation in everyday clinical practice - Henrique Taveira Couto Guedes Vasconcelos (2020)
Aims Neurohormonal (NH) blockade/modulation is the core of Heart Failure with reduced Ejection Fraction (HFrEF) therapy. While improving long-term prognosis, it also induces hyperkalemia, which may increase mortality in the short-term. Thus, hyperkalemia frequently leads to withholding or reducing NH blockade/modulation. This is associated with worsening prognosis. We evaluated the relevance of hyperkalemia as a limiting factor of NH Blockade/Modulation in real-life clinical conditions. Methods and results We reviewed the medical records of HFrEF patients attending a HF clinic at a tertiary Portuguese hospital during 2018 (n=240). We determined the number of patients not tolerating maximal NH blockade/modulation due to hyperkalemia. Hyperkalemia episodes incidence and characteristics were assessed. Only 6 patients (2.5%) reached maximal NH blockade/modulation. Hyperkalemia was the limiting factor in 48 (20%) patients. A total of 185 hyperkalemia episodes occurred in 100 (41.7%) patients. Forty five (24.3%) episodes were moderate or severe (serum K+ ≥ 5.5 mmol/L). Hypertension, diabetes mellitus and renal failure were associated with the occurrence of hyperkalemia. Conclusion In daily clinical practice, hyperkalemia is frequent and limits NH blockade/modulation. Addressing hyperkalemia is an important issue in HFrEF treatment